2008
DOI: 10.1177/1053451208321452
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practices in Special Education: Some Practical Considerations

Abstract: A major tenet of both the Individuals with Disabilities Education Act and the No Child Left Behind Act is the identification and use of evidence-based practices, or those instructional techniques shown by research as most likely to improve student outcomes meaningfully. However, much confusion exists regarding the meaning and potential applications of evidence-based practices in special education. Evidence-based practices are traditionally supported by the findings of multiple, high-quality, experimental resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 10 publications
0
68
0
1
Order By: Relevance
“…These types of research are unique in that they are designed to address whether the independent variable (e.g., an instructional practice) causes change in the dependent variable(s) (e.g., student outcomes; see Cook et al, 2008). That is, when used appropriately, these research designs rule out primary alternative explanations for what may have caused changes in student outcomes other than the practice being examined.…”
Section: Methodsmentioning
confidence: 97%
“…These types of research are unique in that they are designed to address whether the independent variable (e.g., an instructional practice) causes change in the dependent variable(s) (e.g., student outcomes; see Cook et al, 2008). That is, when used appropriately, these research designs rule out primary alternative explanations for what may have caused changes in student outcomes other than the practice being examined.…”
Section: Methodsmentioning
confidence: 97%
“…Although progress has been made to identify effective educational interventions for young children, more research is needed because relatively few EBPs have been identified for use in ECE. While more EBPs are available for general education and special education practices, a research-to-practice gap does exist in these fields as well (Cook et al 2008). Even when EBPs have been identified for use in ECE, they are not yet sufficiently applied in educational settings for young children to guarantee better outcomes: ''considerably greater progress has been made in identifying evidence-based interventions than in implementing these interventions'' (Detrich and Lewis 2012, p. 216).…”
Section: Challenges Of Implementing Evidence-based Practices In Ece Pmentioning
confidence: 97%
“…There is general agreement that there is a range of evidence-based strategies that have been shown to improve academic learning and behaviour of students with disabilities and special education needs (Cook, Tankersley, Cook, & Landrum, 2008;Forness, Kavale, Blum, & Lloyd, 1997;Kutash, Duchnowski, & Lynn, 2009;Odom et al, 2005;Westling, 2010). Cook, Tankersely, and Harjusola-Webb (2008) suggested that 'the notion of using educational practices that have been shown to improve students' learning and behavior outcomes through reliable, trustworthy research seems to be both an essential and principled goal for the field of special education' .…”
Section: Abstract: Special Education Teachers Qualifications Advertmentioning
confidence: 99%